2004
DOI: 10.1577/m03-134.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Considerations in the Management of Atlantic Cod off Nova Scotia, Canada

Abstract: A spatial, age‐structured population dynamics model was developed for a stock of Atlantic cod Gadus morhua off eastern Nova Scotia to examine alternative management options. The model incorporates stock structure, seasonal migration, predation, Allee effects, and variation in natural mortality. The simulated dynamics of two substocks were compared under three management options: (1) historical catch levels; (2) combined management (substocks are managed as one unit) with a constant fishing mortality rate (F) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…When biological processes such as migration underlie fluctuations in catches, changes in fishing mortality may be decoupled from variations in stock size, leading to erroneous estimates of stock status Kell and Fromentin 2007). Fisheries that coincide with overlap in the distribution of multiple stocks (mixed stock fisheries) are particularly vulnerable to mismanagement because a failure to properly account for the occurrence of multiple components within the fishery can lead to overexploitation of lessproductive stocks (Fu and Fanning 2004;Ying et al 2011). Population diversity can dampen fluctuations in abundance and confer stability to the stock complex (Schindler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When biological processes such as migration underlie fluctuations in catches, changes in fishing mortality may be decoupled from variations in stock size, leading to erroneous estimates of stock status Kell and Fromentin 2007). Fisheries that coincide with overlap in the distribution of multiple stocks (mixed stock fisheries) are particularly vulnerable to mismanagement because a failure to properly account for the occurrence of multiple components within the fishery can lead to overexploitation of lessproductive stocks (Fu and Fanning 2004;Ying et al 2011). Population diversity can dampen fluctuations in abundance and confer stability to the stock complex (Schindler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Even with a relatively sedentary flounder species, such as plaice, the importance and degree of movement was easily demonstrated. Many marine species do not maintain isolated populations, violating the main assumption of single-stock assessment models that immigration and emigration are negligible (Hart and Cadrin, 2004) and having important implications for management (e.g., Stephenson, 1999;Secor, 2002;Fu and Fanning, 2004;Maunder, 2005). Aldenberg (1975) suggested that all subpopulations should be assessed together as a unit stock when movement rates between sub-populations are extremely high.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach avoids the cost of identifying and monitoring subpopulations, but risks reduction in productivity as well as loss of genetic diversity. Spatial management of fish species at the level of the stock or population is considered the best approach for conservation of resources (Taylor 1997;Fu and Fanning 2004;Laikre et al 2005). If disproportionate harvest takes place on unrecognized genetic stocks, it may result in overharvest and (or) loss of genetic diversity of some components of the population (e.g., Taylor 1997;Matala et al 2004;Laikre et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…If disproportionate harvest takes place on unrecognized genetic stocks, it may result in overharvest and (or) loss of genetic diversity of some components of the population (e.g., Taylor 1997;Matala et al 2004;Laikre et al 2005). This problem can be exacerbated when genetically distinct stocks with different carrying capacities, natural mortality, or growth rates are managed as a single stock (e.g., Martien et al 2013;Fu and Fanning 2004;Dougherty et al 2013).…”
Section: Introductionmentioning
confidence: 99%